An operational measure of liquidity - John J. McCall; Steven A. Lippman (Universität Konstanz, Fakultät für Wirtschaftswissenschaften und Statistik, 1984)
Economists' view of liquidity is askin to Supreme Court Justice Stewart's View of hard-core pornography: I shall not ... attempt further to define (it) .... But I know it when I see it. Embedding the process of selling an asset in a search environment enables us to provide an exact definition of liquidity: an asset's liquidity is the expected time until it is sold while pursuing an optimal (in the sense of maximization of expected discounted net proceeds) policy. Our analysis reveals that this definition is compatible with most other notions of liquidity and, in particular, with those of Keynes1 , impatience, the discount associated with a quick sale, and predictability.
Keywords: 330